PELATIHAN PEMBUATAN SABUN CAIR (CUCI PIRING DAN CUCI BAJU) PADA KELOMPOK IBU-IBU PKK KELURAHAN TAWANGREJO KECAMATAN KARTOHARJO KOTA MADIUN - Wahidin Nuriana; Tomi Tristono; Fardiana Karuniawati (JURNAL DAYA-MAS, 2025)
Housewives need dishwashing soap and clothes washing soap every day. It would be more economical if these ingredients could be made themselves and would be more economical. The plan for this community service activity is to provide training in making liquid soap which will be carried out in Tawangrejo Village, Kartoharjo District, Madiun City, Madiun, whose are PKK’s member. The aim of this activity is to provide knowledge, insight and assistance in making liquid soap which is used for washing dishes and washing clothes. The methods used in community service activities use presentation and demonstration methods. Community Service Activities have been carried out well and smoothly and the mothers are very enthusiastic and motivated to do it independently. Attended by 30 mothers, 12 participants of the Unmer Madiun KKN, the mothers took part in mixing the soap ingredients, stirring so they took part in the practice of making liquid soap. The result of this service activity was that the participants received products and understood entrepreneurial opportunities in liquid soap products as dishwashing and clothes washing soap